Facultative symbionts are potential agents of symbiont-mediated RNAi in aphids - Li, Tong; Wei, Yongjun; Zhao, Chenchen; Li, Shaojian; Gao, Suxia; Zhang, Yuanchen; Wu, Yuqing; Lu, Chuantao (Frontiers in Microbiology, 2022)
Aphids are major crop pests, and they can be controlled through the application of the promising RNA interference (RNAi) techniques. However, chemical synthesis yield of dsRNA for RNAi is low and costs high. Another sustainable aphid pest control strategy is using symbiont-mediated RNAi (SMR), which can generate dsRNA by engineered microbes. Aphid host the obligate endosymbiont Buchnera aphidicola and various facultative symbionts that not only have a wide host range but are also vertically and horizontally transmitted. Thus, we described the potential of facultative symbionts in aphid pest control by SMR. We summarized the community and host range of these facultative symbionts, and then reviewed their probable horizontal transmitted routes and ecological functions. Moreover, recent advances in the cultivation and genetic engineering of aphid facultative symbionts were discussed. In addition, current legislation of dsRNA-based pest control strategies and their safety assessments were reviewed.